2007
DOI: 10.1074/jbc.m611896200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Ribosomal/Cytochrome c SET Domain Methyltransferase Subfamily

Abstract: Ribosomal protein L23ab is specifically dimethylated at two distinct sites by the SET domain-containing enzyme Rkm1 in the yeast Saccharomyces cerevisiae. Using liquid column chromatography with electrospray-ionization mass spectrometry, we determined that Rpl23ab purified from the ⌬rkm1 deletion strain demonstrated a loss in mass of ϳ56 Da when compared with Rpl23ab purified from the wild type strain. When Rpl23ab was proteolyzed, using proteinase ArgC or CNBr, and the peptides derived were analyzed by tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…If this is the case, at least four S. pombe SET methyltransferases, Set8, Set10, Set11, and Set13, are involved in the modification of ribosomal proteins. In this respect, one hypothesis to explain this is that a subfamily of SET methyltransferases may have evolved to target the lysine residues of highly basic proteins, such as histones and ribosomal proteins, that stably associate with DNAs and RNAs, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this is the case, at least four S. pombe SET methyltransferases, Set8, Set10, Set11, and Set13, are involved in the modification of ribosomal proteins. In this respect, one hypothesis to explain this is that a subfamily of SET methyltransferases may have evolved to target the lysine residues of highly basic proteins, such as histones and ribosomal proteins, that stably associate with DNAs and RNAs, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the budding yeast Saccharomyces cerevisiae, direct mass spectrometric analysis of the large ribosomal proteins revealed that six of them, Rpl1, Rpl3, Rpl12, Rpl23, Rpl42, and Rpl43, are post-translationally modified by the addition of methyl groups (14). Rpl23 is specifically ⑀-N-dimethylated at two residues, Lys 105 and Lys 109 , and these modifications are catalyzed by the SET domain-containing methyltransferase Rkm1 (15,16). S. cerevisiae Rpl12, the counterpart of bacterial L11, is also modified,: by ⑀-N-dimethylated at Lys 3 , ⑀-N-trimethylation at Lys 10 , and ␦-N-monomethylation at Arg 66 (17,18).…”
mentioning
confidence: 99%
“…Interestingly, the majority of the yeast point mutations displaying phenotypes 3 H-methylated large ribosomal subunits were isolated from [ 3 H]AdoMetlabeled intact BY4742 wild-type cells and reverse-phase HPLC was used to isolate a fraction containing a mixture of Rpl3 and Rpl23ab as described in "Experimental Procedures." The latter protein is a known coeluting species known to contain two dimethyllysine residues (17). This mixture was acid hydrolyzed and 1 mol each of ⑀-dimethyllysine and 3-methyl-L-histidine (-methyl-L-histidine, Vega Biochemicals 12608) standards were added.…”
Section: ϫ13mentioning
confidence: 99%
“…We have used mass spectrometry to screen for loss of methylation in the intact ribosomal proteins of yeast strains lacking a single known or putative methyltransferase. Using this approach, SET-domain methyltransferases responsible for modifying Rpl12ab, Rpl23ab, Rpl42ab, and eEF1a at specific lysine residues have been identified (13)(14)(15)(16)(17). In addition to screening the SET-domain methyltransferase gene knock-out strains, we also screened the seven ␤-strand methyltransferase gene family for loss of methylation in gene deletions.…”
mentioning
confidence: 99%
“…Rpl3 is modified to form a 3-methylhistidine residue at position 243 (13), whereas Rpl12ab is modified at three positions: a dimethylproline residue is present at the N terminus (14), an ⑀-trimethyllysine residue is found at position 3 (9,19), and an unusual ␦-monomethylarginine residue is found at position 66 (2). Rpl23ab is modified by ⑀-dimethyllysine formation at positions 105 and 109 (7), and Rpl42ab is modified by ⑀-monomethyllysine formation at positions 39 and 55 (9). The proposed methylation at Rpl43ab has not been observed to date in our studies.…”
mentioning
confidence: 99%